The development of a consumer-acceptable product for the nutritional supplementation of black preschool children - Westdyk, Beatra(Beatrix Hendrina) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. in Home Economics) -- University of Stellenbosch, 1997.